Cardiovascular diseases among people living with HIV/AIDS in Ethiopia: A scoping review - Dawit Errega; Marios Kantaris; Andualem Deresse; Kaleab Berhanu; Yohannes Gebreegziabhere; Sisay Mulugeta Alemu (PLoS ONE, 2026)
Background Human Immunodeficiency Virus (HIV)/ Acquired Immunodeficiency Syndrome (AIDS) remains a significant burden in Ethiopia. People living with HIV/AIDS (PLWHA) are at increased risk of cardiovascular diseases due to both the virus and the side effects of antiretroviral therapy. Despite a growing body of research on cardiovascular diseases in PLWHA in Ethiopia, no review has synthesised the available evidence. This scoping review aims to summarise the existing literature on cardiovascular diseases among PLWHA in Ethiopia. Methods This scoping review followed the Arksey and O’Malley (2005) framework, with enhancements from Levac et al. (2010). A systematic search was conducted across six electronic databases (PubMed, EMBASE, ProQuest, Global Index Medicus, and Web of Science) in November 2023 and updated in March 2026. Studies on cardiovascular diseases among PLWHA in Ethiopia were included. Two reviewers independently screened titles, abstracts, and full texts. A data extraction template was used, and findings were synthesised narratively. The selection process was documented using a PRISMA flow diagram. Results Twenty-six studies were included, with nearly two-thirds (61.5%, n = 16) focused on hypertension. The prevalence of hypertension among PLWHA in Ethiopia ranged from 11.0 to 41.3%. Factors associated with hypertension included male gender, old age, rural residence, alcohol consumption, smoking, family history, low physical activity, obesity, and HAART duration/type. Other cardiovascular conditions studied included ischemic stroke, dilated cardiomyopathy, ECG abnormalities, atherosclerotic cardiovascular disease, and pericardial effusion. Most studies were cross-sectional and institution-based. Conclusion This review highlights the limited yet growing evidence on cardiovascular diseases among PLWHA in Ethiopia, with a predominant focus on hypertension. Future research should use more robust study designs, such as longitudinal and interventional studies, encompass a broader range of cardiovascular diseases, and include community-based studies to better understand the prevalence and burden of cardiovascular diseases among PLWHA in Ethiopia.